Lithium ion battery cathode material and preparation method thereof
Patent Information
- Application Number
- CN202611133082.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-28
- Publication Date
- 2026-10-16
AI Technical Summary
[0003]目前,可将碳酸盐共沉淀前驱体与锂源和掺杂源混合,并将混合物经一次烧结、包覆剂包覆和二次烧结制备出锂离子电池正极材料,在制备过程中,受烧结的不完全性的影响,锂原子与碳酸盐共沉淀前驱体不能良好反应,导致制备出的锂离子电池正极材料的性能较差
[0014]本申请至少具有如下有益效果:在500~700 ℃下对碳酸盐共沉淀前驱体进行预烧结,主要反应方程式为:
Smart Images

Figure CN122930809A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of lithium-ion battery materials, and in particular to a lithium-ion battery cathode material and its preparation method. Background Technology
[0002] Lithium-ion batteries are widely used in portable electronic devices, electric vehicles, and energy storage systems due to their advantages such as high energy density, long cycle life, and low self-discharge rate. Among them, ternary cathode materials occupy an important position in lithium-ion batteries due to their high specific capacity, low cost, and relatively low material cost.
[0003] Currently, lithium-ion battery cathode materials can be prepared by mixing carbonate coprecipitation precursors with lithium sources and doping sources, and then subjecting the mixture to primary sintering, coating with a coating agent, and secondary sintering. However, due to the incomplete sintering process, lithium atoms cannot react well with the carbonate coprecipitation precursors, resulting in poor performance of the prepared lithium-ion battery cathode materials. Summary of the Invention
[0004] The first aspect of this application provides a method for preparing a lithium-ion battery cathode material, comprising the following steps: Pre-sintering step: The carbonate coprecipitation precursor is pre-sintered at 500~700 °C, wherein the chemical formula of the carbonate coprecipitation precursor is […]. , 0<x<1, 0<y<1, 0<1-xy<1; Crushing step: Crushing the pre-sintered product; Mixing step: The pulverized product is mixed with the lithium source and the doping source; One-time sintering step: The mixed product is sintered once; Coating step: The product after one sintering is coated with a coating agent; Secondary sintering step: The coated product is sintered a second time.
[0005] In some embodiments, during the pre-sintering step, the carbonate coprecipitation precursor is held at 500-700°C for 5-8 hours.
[0006] In some embodiments, during the pulverization step, the product is controlled to satisfy: 1 μm ≤ D50 ≤ 2 μm, 4 μm ≤ D100 ≤ 6 μm.
[0007] In some embodiments, during the coating step, the product after the first sintering is dispersed, and the coating agent is uniformly sprayed onto the product after the first sintering. The coating agent is formed by dispersing a coating material in deionized water. The coating material is... , , At least one of the following, wherein the mass of the coating agent is 0.05 to 0.5% of the mass of the product after the first sintering.
[0008] In some embodiments, during the mixing step, the dopant source is , , , At least one of the following, wherein the mass of a single dopant in the doping source is 0.03 to 0.3% of the mass of the carbonate coprecipitation precursor.
[0009] In some embodiments, during the first sintering step, the mixed product is held at 900-960 °C for 5-10 hours, with the heating rate controlled at 2-5 °C / min and the cooling rate controlled at 2-4 °C / min. In the secondary sintering step, the coated product is held at 700~750 ℃ for 8~10 hours, with the heating rate controlled at 3~6 ℃ / min and the cooling rate controlled at 2~4 ℃ / min.
[0010] In some embodiments, the method for preparing the lithium-ion battery cathode material further includes: Heat preservation step: After the secondary sintering step, heat preservation is carried out for 5 to 8 hours when the temperature drops to 400~450 ℃.
[0011] In some embodiments, in the mixing step, the dopant source is first dispersed using a dispersant, and then the pulverized product is mixed with the lithium source and the dopant source, wherein the mass of the dispersant is 0.01 to 0.1% of the mass of the carbonate coprecipitation precursor.
[0012] The second aspect of this application provides a lithium-ion battery cathode material, which is prepared using the lithium-ion battery cathode material preparation method in any of the above embodiments.
[0013] In some embodiments, the lithium-ion battery cathode material has a 1C discharge capacity ≥178 mAh / g and a cycle capacity retention rate ≥93% after 100 cycles.
[0014] This application has at least the following beneficial effects: Pre-sintering of carbonate coprecipitation precursors at 500~700 °C, the main reaction equation being: Due to the presence of multiple valence states in metals, the above reaction equations are not balanced, where 1≤m≤1.5.
[0015] On the one hand, a temperature of 500~700 ℃ is high enough to meet the threshold for complete decomposition of the carbonate coprecipitation precursor, thus maximizing the decomposition of the precursor. The release process also simultaneously evaporates the moisture from the carbonate co-precipitation precursor, thus preventing moisture loss during subsequent sintering. And water vapor blocks oxygen, There is sufficient oxygen and Contact with the lithium source helps to make the reaction more complete; on the other hand, the temperature of 500~700 ℃ is low enough to effectively prevent the crystallization of the carbonate coprecipitation precursor. The degree of crystallization is low, which is conducive to the full reaction with the lithium source in subsequent steps.
[0016] In addition, performing the pulverization step first can eliminate the situation where the uneven proportion of nickel, cobalt and manganese in the pre-sintered product leads to the subsequent local lithium imbalance; performing the mixing step afterwards is conducive to the full mixing of the pulverized product with the lithium source and doping source, which is beneficial to the more complete reaction in the subsequent sintering step.
[0017] In summary, this application enables a more complete reaction and improves the performance of lithium-ion battery cathode materials. Attached Figure Description
[0018] Figure 1 This is a comparison graph showing the rate performance of the lithium-ion battery cathode materials of this application with those of the embodiments and comparative examples.
[0019] Figure 2 This is a comparison graph showing the cycle performance of the lithium-ion battery cathode material of this application with that of the embodiments and comparative examples.
[0020] Figure 3 The images are scanning electron microscope (SEM) images of the lithium-ion battery cathode materials of this application at a magnification of 3,000x.
[0021] The following detailed description, in conjunction with the accompanying drawings, will further illustrate this application. Detailed Implementation
[0022] The technical solutions in the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments.
[0023] References to "one embodiment" or "some embodiments" as described in this specification mean that at least one embodiment of this application includes a specific feature, structure, or characteristic described in connection with that embodiment. Therefore, phrases such as "in one embodiment," "in some embodiments," "in other embodiments," "in still other embodiments," etc., appearing in different parts of this specification do not necessarily refer to the same embodiment, but rather mean "at least one, but not all, embodiments," unless otherwise specifically emphasized. The terms "comprising," "including," "having," and variations thereof mean "including, but not limited to," unless otherwise specifically emphasized.
[0024] The term "smaller value ~ larger value" used in this application, unless otherwise specified, includes both ends of the range. For example, 1 ~ 5 includes the values 1 and 5.
[0025] The chemical formula of the positive electrode material for lithium-ion batteries is: In the formula, a is the molar ratio of Li ions to the sum of transition metals Ni, Co and Mn in the precursor, which can also be called the molar ratio of Li ions to the precursor. Depending on the actual needs, its value can be 1, 1.03, 1.05 or 1.08.
[0026] The preparation method of lithium-ion battery cathode material includes the following steps: Pre-sintering step: The carbonate coprecipitation precursor is pre-sintered at 500~700 °C, wherein the chemical formula of the carbonate coprecipitation precursor is […]. , 0<x<1, 0<y<1, 0<1-xy<1; Crushing step: Crushing the pre-sintered product; Mixing step: The pulverized product is mixed with the lithium source and the doping source; One-time sintering step: The mixed product is sintered once; Coating step: The product after one sintering is coated with a coating agent; Secondary sintering step: The coated product is sintered a second time. The product after secondary sintering includes lithium-ion battery cathode material.
[0027] The pre-sintering step, the primary sintering step, and the secondary sintering step all include a heating process, a holding process, and a cooling process. The chemical formula of the carbonate co-precipitation precursor can be... , ,or or wait.
[0028] The carbonate coprecipitation precursor was pre-sintered at 500~700 ℃, and the main reaction equations are as follows: Due to the presence of multiple valence states in metals, the above reaction equations are not balanced, where 1≤m≤1.5.
[0029] On the one hand, a temperature of 500~700 ℃ is high enough to meet the threshold for complete decomposition of the carbonate coprecipitation precursor, thus maximizing the decomposition of the precursor. The release process also simultaneously evaporates the moisture from the carbonate co-precipitation precursor, thus preventing moisture loss during subsequent sintering. And water vapor blocks oxygen, There is sufficient oxygen and Contact with a lithium source helps to make the reaction more complete, with the lithium source as... For example, The main reaction equations for the primary sintering with the lithium source are: Due to the presence of multiple valence states in metals, the above reaction equation is not balanced, where 1.5 ≤ n ≤ 2.
[0030] On the other hand, a temperature of 500~700 ℃ is low enough to effectively prevent the crystallization of carbonate coprecipitation precursors, resulting in a low degree of crystallization, which is beneficial for full reaction with the lithium source in subsequent steps.
[0031] In some embodiments, the pre-sintering temperature is 600~700 °C. By increasing the pre-sintering temperature, on the one hand, the reaction rate and the degree of decomposition of the carbonate coprecipitation precursor can be increased, making the decomposition of the carbonate coprecipitation precursor more complete, and on the other hand, the reaction rate and the degree of decomposition of the carbonate coprecipitation precursor can be increased. On the one hand, it allows for complete discharge; on the other hand, it enables more complete diffusion of elements, which is beneficial for a full reaction with the lithium source in subsequent steps.
[0032] Furthermore, when preparing carbonate coprecipitation precursors using the carbonate coprecipitation process, the nickel, cobalt, and manganese ratios of small and large carbonate coprecipitation precursors are inconsistent due to the crystal growth mechanism. By first performing a pulverization step, the pre-sintered product can be ground up, ensuring a uniform distribution of nickel, cobalt, and manganese. This eliminates the subsequent local lithium imbalance caused by the uneven nickel, cobalt, and manganese ratios in the pre-sintered product. The subsequent mixing step facilitates thorough mixing of the pulverized product with the lithium source and dopant source, preventing local deviations in the lithium-to-nickel, cobalt, and manganese ratios. This improves the uniformity and stability of the mixed product, leading to a more complete reaction in the subsequent sintering step.
[0033] Meanwhile, by employing a high-temperature multi-stage sintering process and precisely controlling the heat treatment path, excellent growth of single crystal particles was ensured, further improving the grain uniformity and density of the lithium-ion battery cathode material, thereby enhancing the conductivity and stability of the lithium-ion battery cathode material.
[0034] In summary, the method for preparing lithium-ion battery cathode materials in this application enables a more complete reaction and improves the performance of lithium-ion battery cathode materials.
[0035] In some embodiments, the method for preparing lithium-ion battery cathode materials further includes a heat preservation step, which is located after the secondary sintering step. In the heat preservation step, the product after secondary sintering is kept at a temperature lower than the secondary sintering temperature. By incorporating the heat preservation step, the cooling time of the product after secondary sintering can be extended, and the process of cooling the product to room temperature after secondary sintering can be divided into two stages, reducing the temperature reduction of a single cooling operation. This avoids stress cracking of the product after secondary sintering due to excessively rapid cooling, thereby improving the quality of the lithium-ion battery cathode material.
[0036] In some embodiments, during the pre-sintering step, the carbonate coprecipitation precursor is held at 500-700°C for 5-8 hours to ensure... Fully release energy and avoid excessively long pre-sintering time, which would affect production efficiency and waste energy.
[0037] In some embodiments, during the pulverization step, the product is controlled to meet the following conditions: 1 μm ≤ D50 ≤ 2 μm, 4 μm ≤ D100 ≤ 6 μm, to ensure complete pulverization. Here, D50 represents the median particle size, meaning that 50% of the particles have a particle size smaller than D50; D100 represents the maximum particle size, meaning that 100% of the particles have a particle size smaller than D100.
[0038] In some embodiments, D50 can be 1 μm, 1.5 μm or 2 μm, etc., and D100 can be 4 μm, 5 μm or 6 μm, etc. The smaller the values of D50 and D100, the smaller the particle size of the pulverized product and the more thorough the pulverization.
[0039] In some embodiments, the lithium source in the mixing step can be LiOH At least one of them, and may also be other lithium salts, the molar ratio of the pulverized product to lithium ions is 1:1.00~1.08, for example 1:1.00, 1:1.03, 1:1.05 or 1:1.08, etc.; , , , The doped material is formed by the doping source being... , , , At least one of the following, wherein the mass of a single dopant in the doping source is 0.03 to 0.3% of the mass of the carbonate coprecipitation precursor, for example, 0.03%, 0.05%, 0.1% or 0.3%.
[0040] Al is used to improve thermal stability, Mg to stabilize the layered structure, Ti to improve ionic conductivity, and B to lower the sintering energy barrier and act as a flux. The doping source is determined according to actual needs. or or or Or, it may include two, three, or all four of the above four types.
[0041] In some embodiments, during the first sintering step, the mixed product is held at 900-960 °C for 5-10 hours, with the heating rate controlled at 2-5 °C / min and the cooling rate controlled at 2-4 °C / min.
[0042] The temperature during the first sintering can be 900 ℃, 920 ℃ or 960 ℃, etc., the heating rate during the first sintering can be 2 ℃ / min, 3 ℃ / min, 4 ℃ / min or 5 ℃ / min, etc., and the holding time can be 5 hours, 7 hours, 9 hours or 10 hours, etc.; during the cooling process after holding, the cooling rate can be 2 ℃ / min, 3 ℃ / min or 4 ℃ / min, etc.
[0043] In some embodiments, during the coating step, the product after the first sintering is wet-coated using the coating agent.
[0044] In the coating step, the product after the first sintering is dispersed, and the coating agent is uniformly sprayed onto the product after the first sintering. The coating agent is formed by dispersing a coating material in deionized water. The coating material is... , , At least one of them, for example or or Or, a combination of two or three of them. The mass of the coating agent is 0.05 to 0.5% of the mass of the product after the first sintering.
[0045] In other embodiments, dry coating can also be used, that is, directly coating the powdered coating agent onto the product after the first sintering. In this case, the coating agent can be... , , At least one of them.
[0046] The purpose of coating is to form a uniform and dense protective layer on the product after primary sintering to suppress side reactions. In the product after primary sintering, the particle size distribution of the particles after the pulverization step is relatively dispersed. Wet coating can more uniformly coat the product after primary sintering, improving the coating effect and forming a uniform and dense protective layer on the surface of the product. This significantly improves the uniformity and density of the particles, enhances the long-term performance of the lithium-ion battery cathode material, and improves its mechanical strength and stability. Dry coating is a simpler process and does not require the treatment of waste liquid caused by the introduction of deionized water.
[0047] In some embodiments, during the secondary sintering step, the coated product is held at 700-750 °C for 8-10 hours, with the heating rate controlled at 3-6 °C / min and the cooling rate controlled at 2-4 °C / min.
[0048] The temperature during the secondary sintering can be 700 ℃, 720 ℃, 740 ℃ or 750 ℃, the heating rate can be 3 ℃ / min, 4 ℃ / min, 5 ℃ / min or 6 ℃ / min, the holding time can be 8 hours, 9 hours or 10 hours, etc.; during the cooling process after holding, the cooling rate can be 2 ℃ / min, 3 ℃ / min or 4 ℃ / min, etc.
[0049] In some embodiments, the method for preparing the lithium-ion battery cathode material further includes: The heat preservation step, following the secondary sintering step, involves holding the temperature at 400-450°C for 5-8 hours. The heat preservation temperature can be 400°C, 420°C, 440°C, or 450°C, and the holding time can be 5, 6, 7, or 8 hours. During the cooling process after heat preservation, the cooling rate can be 2°C / min, 3°C / min, or 4°C / min.
[0050] In some embodiments, during the mixing step, the dopant source is first dispersed using a dispersant, and then the pulverized product is mixed with the lithium source and the dopant source. The mass of the dispersant is 0.01 to 0.1% of the mass of the carbonate coprecipitation precursor, to ensure more thorough mixing of the dopant source with the lithium source and the pulverized product. The dispersant can be deionized water.
[0051] Example 1 The preparation method of lithium-ion battery cathode material includes the following steps: Pre-sintering step: The carbonate coprecipitation precursor is pre-sintered at 600 °C for 6 hours, wherein the chemical formula of the carbonate coprecipitation precursor is […]. .
[0052] Pulverization step: The pre-sintered product is pulverized by sand milling to 1 μm≤D50≤2 μm, 4 μm≤D100≤6 μm.
[0053] Mixing step: The pulverized product is mixed with the lithium source Mix at a molar ratio of 1:1.05, and simultaneously... , and As a doping source, following the formula of carbonate co-precipitation precursor + lithium source: : : The mass ratio of the doping material is 1:0.1%:0.1%:0.1%, and the mixture is stirred for 10-20 minutes using a high-speed mixer to ensure that the pulverized product, lithium source, and dopant source are fully and uniformly mixed.
[0054] First sintering step: The mixed product is kept at 930 ℃ for 8 hours to obtain the product after first sintering.
[0055] Coating step: The product after one sintering is dispersed in a high-speed mixer at 1400 rpm for 10-15 minutes, and the coating material is dispersed in deionized water to prepare a slurry with a solid content of 0.4%. This slurry constitutes the coating agent. The coating agent is sprayed onto the material after one sintering using a spray drying device.
[0056] Among them, the coating material is and And according to the product after one sintering: : Weigh out the coating material at a mass ratio of 1:0.05%:0.05%.
[0057] Secondary sintering step: The coated product is kept at 730 ℃ for 8 hours; Heat preservation step: After the temperature drops from 730 ℃ to 425 ℃, the product after secondary sintering is kept at 425 ℃ for 6 hours.
[0058] The heating and cooling rates in the primary sintering step, the secondary sintering step, and the heat preservation step are as described above.
[0059] Please see Figure 1 The charge / discharge rate (Capacity, C), also known as 1C, represents a complete discharge within one hour. The 1C discharge capacity of the positive electrode material in a lithium-ion battery is 178.94 mAh / g. Please refer to [link / reference]. Figure 2 The capacity retention rate of the positive electrode material for lithium-ion batteries is greater than 95% after 100 cycles.
[0060] Example 2 The difference between Example 2 and Example 1 is that in Example 2, the temperature of the secondary sintering step is adjusted from 730 ℃ to 750 ℃, and the holding time is adjusted from 8 hours to 5 hours. The remaining steps of Example 2 are the same as those of Example 1.
[0061] Example 3 The difference between Example 3 and Example 1 is that in Example 3, the pre-sintering temperature is adjusted from 600 °C to 550 °C during the pre-sintering step. In Example 3, the holding time during the pre-sintering step remains 6 hours, and the chemical formula of the carbonate co-precipitation precursor remains the same. The remaining steps of Example 3 are the same as those of Example 1.
[0062] Example 4 The difference between Example 4 and Example 1 is that in Example 4, the pre-sintering temperature is adjusted from 600 °C to 500 °C, and the holding time is 8 hours. In Example 4, the chemical formula of the carbonate co-precipitation precursor remains the same. The remaining steps of Example 4 are the same as those of Example 1.
[0063] Example 5 The difference between Example 5 and Example 1 is that in Example 5, the pre-sintering temperature is adjusted from 600 °C to 700 °C, and the holding time is 5 hours. In Example 5, the chemical formula of the carbonate co-precipitation precursor remains the same. The remaining steps of Example 5 are the same as those of Example 1.
[0064] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that in Comparative Example 1, there is no pulverization step; instead, a mixing step is performed directly after the pre-sintering step, in which the pre-sintered product is mixed with the lithium source and the doping source. The remaining steps of Comparative Example 1 are the same as those of Example 1.
[0065] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that in Comparative Example 2, there is no pre-sintering step; instead, the carbonate coprecipitation precursor is directly pulverized in the pulverization step. The remaining steps of Comparative Example 2 are the same as those of Example 1.
[0066] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that in Comparative Example 3, a dry coating method is used in the coating step. The product after one sintering is dispersed in a high-speed mixer at 1400 rpm for 5 minutes, and the coating agent is coated onto the product after one sintering. The coating material is... and The products after one sintering are categorized by mass ratio: : Weigh out the coating material at a ratio of 1:0.05%:0.05%, and mix the coating materials to form a coating agent. The remaining steps of Comparative Example 3 are the same as those of Example 1.
[0067] Electrochemical performance tests of coin cells were conducted on Examples 1, 2, 3, 4, and 5, as well as Comparative Examples 1, 2, and 3, under the following conditions: The prepared lithium-ion battery cathode material, conductive carbon, and binder polyvinylidene fluoride (PVDF) were mixed uniformly at a mass ratio of 90:5:5 to form a half-cell. Constant current charge-discharge tests were performed using a Blue Battery testing system. During the tests, the initial discharge capacity test operating voltage range was 2.8V~4.4V, the charge-discharge rate was +0.1C / -0.1C, meaning the charge-discharge was completed in 10 hours, and the constant voltage (CV) cutoff current was 0.01C. The high-temperature cycling test operating voltage range was 2.8V~4.4V, the temperature was 45℃, the charge-discharge rate was +1C / 1C, and the CV cutoff current was 0.01C.
[0068] The test results are as follows: Please refer to [link / reference]. Figure 1 During the initial 0.1C charge, the performance of each embodiment and comparative example was basically the same. During the initial 0.1C and 1C discharge, the height of the bar charts corresponding to Embodiments 1 to 5 and Comparative Example 3 was consistently higher than the height of the bar charts corresponding to Comparative Example 1 and Comparative Example 2, and the 1C discharge capacity of the lithium-ion battery cathode material was ≥178 mAh / g. Therefore, the short-term rate performance of the lithium-ion battery cathode materials in Embodiments 1 to 5 and Comparative Example 3 was superior to that in Comparative Example 1 and Comparative Example 2. Please refer to... Figure 2 The absolute values of the slopes of the curves corresponding to Examples 1 to 5 are smaller than the absolute values of the slopes of the curves corresponding to Comparative Examples 1, 2, and 3. As the number of cycles increases, the battery capacity decay rate of the half-cell made with the lithium-ion battery cathode material in Examples 1 to 5 is smaller, and the cycle capacity retention rate of the lithium-ion battery cathode material after 100 cycles is ≥93%. In particular, the battery capacity decay rate of the half-cell made with the lithium-ion battery cathode material in Comparative Example 3 is the largest. Therefore, the long-term cycle performance of the lithium-ion battery cathode materials prepared in Examples 1 to 5 is better than that of the lithium-ion battery cathode materials prepared in Comparative Examples 1, 2, and 3.
[0069] Please see Figure 3The lithium-ion battery cathode material prepared in Example 1 has more uniform grains and better density, so the performance of the lithium-ion battery cathode material prepared in Example 1 is also better.
[0070] The reasons for the poor performance of the lithium-ion battery cathode material prepared in the comparative example are as follows: In Comparative Example 1, the pulverization step was not performed, resulting in a wide distribution of single-crystal particles in the prepared lithium-ion battery cathode material. Some single-crystal particles failed to grow, leading to poor performance of the lithium-ion battery cathode material.
[0071] In Comparative Example 2, the pre-sintering step was not performed, resulting in a large number of ungrown single crystal particles in the prepared lithium-ion battery cathode material, leading to poor performance of the lithium-ion battery cathode material.
[0072] In Comparative Example 3, dry coating was used in the coating step. Compared with wet coating, dry coating has poor coating uniformity and agglomerates of coating material particles, resulting in poor long-term performance of lithium-ion battery cathode material.
[0073] This application also provides a lithium-ion battery cathode material, which can be prepared by the lithium-ion battery cathode material preparation method in any of the above embodiments. The lithium-ion battery cathode material has a 1C discharge capacity ≥178 mAh / g and a cycle capacity retention rate ≥93% after 100 cycles, which can significantly improve the energy density and cycle life of lithium-ion batteries.
[0074] The above embodiments are only used to illustrate the technical solutions of this application and are not intended to limit it. Although this application has been described in detail with reference to the above preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions to the technical solutions of this application should not depart from the spirit and scope of the technical solutions of this application.
Claims
1. A method for preparing a lithium-ion battery cathode material, characterized in that, Includes the following steps: Pre-sintering step: The carbonate coprecipitation precursor is pre-sintered at 500~700 °C, wherein the chemical formula of the carbonate coprecipitation precursor is […]. ,0<x<1, 0<y<1, 0<1-xy<1; Crushing step: Crushing the pre-sintered product; Mixing step: The pulverized product is mixed with the lithium source and the doping source; One-time sintering step: The mixed product is sintered once; Coating step: The product after one sintering is coated with a coating agent; Secondary sintering step: The coated product is sintered a second time.
2. The method for preparing the lithium-ion battery cathode material as described in claim 1, characterized in that, In the pre-sintering step, the carbonate coprecipitation precursor is kept at 500~700 °C for 5~8 hours.
3. The method for preparing the lithium-ion battery cathode material as described in claim 1, characterized in that, In the pulverization step, the product is controlled to meet the following conditions: 1 μm ≤ D50 ≤ 2 μm, 4 μm ≤ D100 ≤ 6 μm.
4. The method for preparing lithium-ion battery cathode material according to any one of claims 1 to 3, characterized in that, In the coating step, the product after the first sintering is dispersed, and the coating agent is uniformly sprayed onto the product after the first sintering. The coating agent is formed by dispersing a coating material in deionized water. The coating material is... , , At least one of the following, wherein the mass of the coating agent is 0.05 to 0.5% of the mass of the product after the first sintering.
5. The method for preparing lithium-ion battery cathode material according to any one of claims 1 to 3, characterized in that, In the mixing step, the dopant source is , , , At least one of the following, wherein the mass of a single dopant in the doping source is 0.03 to 0.3% of the mass of the carbonate coprecipitation precursor.
6. The method for preparing the lithium-ion battery cathode material according to any one of claims 1 to 3, characterized in that, In the first sintering step, the mixed product is held at 900~960 ℃ for 5~10 hours, and the heating rate is controlled at 2~5 ℃ / min, and the cooling rate is controlled at 2~4 ℃ / min. In the secondary sintering step, the coated product is kept at 700~750 ℃ for 8~10 hours, and the heating rate is controlled at 3~6 ℃ / min, and the cooling rate is controlled at 2~4 ℃ / min.
7. The method for preparing the lithium-ion battery cathode material as described in claim 6, characterized in that, The method for preparing the lithium-ion battery cathode material further includes: Heat preservation step: After the secondary sintering step, heat preservation is carried out for 5 to 8 hours when the temperature drops to 400~450 ℃.
8. The method for preparing lithium-ion battery cathode material according to any one of claims 1 to 3, characterized in that, In the mixing step, the dopant source is first dispersed using a dispersant, and then the pulverized product is mixed with the lithium source and the dopant source. The mass of the dispersant is 0.01 to 0.1% of the mass of the carbonate coprecipitation precursor.
9. A lithium-ion battery cathode material, characterized in that, It is prepared by the method for preparing lithium-ion battery cathode material according to any one of claims 1 to 8.
10. The lithium-ion battery cathode material as described in claim 9, characterized in that, The lithium-ion battery cathode material has a 1C discharge capacity ≥178 mAh / g and a cycle capacity retention rate ≥93% after 100 cycles.